Acceptability, Feasibility, and Utility of Integrating Pharmacogenetic Testing into a Child Psychiatry Clinic. Issue 2 (9th November 2020) - Claudio‐Campos, Karla; Padrón, Adaixa; Jerkins, Gabriel; Nainaparampil, Jaison; Nelson, Robyn; Martin, Anna; Wiisanen, Kristin; Smith, D. Max; Strekalova, Yulia; Marsiske, Michael; Cicali, Emily J.; Cavallari, Larisa H.; et al.
Abstract : Pharmacogenetic (PGx) testing is a tool to identify patients at a higher risk of adverse events or treatment failure. The concern for unwanted side effects can limit medication adherence, particularly in children and adolescents. We conducted a pragmatic study to evaluate the acceptability and feasibility and gather pilot data on the utility of PGx testing in a child and adolescent psychiatry clinic. Both physicians and families participated in the study and answered pre‐survey and post‐survey questionnaires to examine their attitudes toward PGx testing. Patients were randomized into implementation ( N = 25) and control groups ( N = 24) and underwent PGx testing at the beginning or end of the study, respectively. Clinical consult notes with genotype‐guided recommendations were provided to physicians for their consideration in clinical decisions. Patient‐reported symptom severity and antidepressant‐related side effects were assessed at baseline and for 12 weeks. Both participating physicians and families agreed that PGx testing is a useful tool to improve medication selection. The time from sample collection to having PGx test results was 10 days and 15 days to having consult notes available, which may have impaired test utility in clinical decision making. There were no differences in any clinical end point between the implementation and control arms; however, there were higher antidepressant side effect scores for CYP2D6 poor and intermediate metabolizers after the eighth week of treatment. Our findings revealed benefits and pitfalls with the use of PGx testing in the real‐world clinical setting, which may inform the methodology of a larger trial focused on outcomes.